Enhanced Upper Extremity Functions with a Single Session of Action-Observation-Execution and Accelerated Skill Acquisition Program in Subacute Stroke. (12th June 2018) - Adhikari, Shambhu Prasad; Tretriluxana, Jarugool; Chaiyawat, Pakaratee; Jalayondeja, Chutima
Abstract : Background . Action-observation-execution (AOE) primes physical training. We examined the immediate effect of AOE with accelerated skill acquisition program (ASAP) on dexterity in subacute stroke. Methods . Twelve individuals from 1 to 6 months after stroke were allocated into two groups by matching age and side of stroke. After AOE of 30 minutes, the experimental group received ASAP for 60 minutes whereas the control group received dose-equivalent usual care. The movement time (MT) and functional ability (FA) of hand items of the Wolf motor function test (WMFT), hand functions and global recovery of stroke impact scale (SIS), and intrinsic motivation items of stroke rehabilitation motivation scale were assessed at baseline, after training, and during one-week follow-up. Data were analyzed within and between the groups. Results . AOE significantly decreased MT of flipping cards of WMFT and hand functions of SIS. Total MT was markedly reduced. AOE with ASAP demonstrated significant group-by-time interactions on MT of lifting pencil of WMFT, total MT, and global recovery. Grip strength, FA, and hand functions were significantly improved only in the experimental group. Both groups improved motivation significantly. Conclusions . The AOE with ASAP enhanced dexterity, which persisted for at least a week. This intervention might improve dexterity in subacute stroke. Trial Registration Number . This trial is registered withTCTR20161007001 .